2019
DOI: 10.1080/2162402x.2019.1673129
|View full text |Cite
|
Sign up to set email alerts
|

The promise of adoptive cellular immunotherapies in hepatocellular carcinoma

Abstract: Hepatocellular Carcinoma (HCC) is one of the leading causes of cancer-related mortality worldwide. Current systemic therapies result only in modest benefits and new therapeutic options are critically needed. Some patients show promising clinical responses to immune checkpoint inhibitors, however, additional immunotherapeutic approaches, such as adoptive cell therapies (ACT), need to be developed. This review summarizes recent ACT studies and discusses the promise and obstacles of this approach. We further disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 62 publications
0
25
0
Order By: Relevance
“…Moreover, clinical trials of CAR-T-cells for solid tumors have been recently launched after proving efficacy in hematologic diseases [50]. Their clinical development in HCC and hepatoblastoma followed promising results from pre-clinical studies and mostly involves AFP, glypican-3, epithelial growth factor receptor, and HBV antigens (NCT03618381; NCT04093648) [51]. However, preliminary trials in HCC showed modest anti-tumor responses [51,52].…”
Section: Combinations Of Icis and Other Immunotherapiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, clinical trials of CAR-T-cells for solid tumors have been recently launched after proving efficacy in hematologic diseases [50]. Their clinical development in HCC and hepatoblastoma followed promising results from pre-clinical studies and mostly involves AFP, glypican-3, epithelial growth factor receptor, and HBV antigens (NCT03618381; NCT04093648) [51]. However, preliminary trials in HCC showed modest anti-tumor responses [51,52].…”
Section: Combinations Of Icis and Other Immunotherapiesmentioning
confidence: 99%
“…Their clinical development in HCC and hepatoblastoma followed promising results from pre-clinical studies and mostly involves AFP, glypican-3, epithelial growth factor receptor, and HBV antigens (NCT03618381; NCT04093648) [51]. However, preliminary trials in HCC showed modest anti-tumor responses [51,52]. Strategies such as identifying more immunogenic antigens, improving T cells tumor penetration, and combining CAR-T cells with other antitumor drugs are explored to improve the efficacy of these immune strategies in HCC and reduce the risk of fatal adverse events (e.g., cytokine release syndrome) [51].…”
Section: Combinations Of Icis and Other Immunotherapiesmentioning
confidence: 99%
See 1 more Smart Citation
“…It has since been approved for treatment in certain types of non-Hodgkin lymphoma including aggressive, relapsed or refractory, diffuse large B cell lymphoma, primary mediastinal B-cell lymphoma, high grade B-cell lymphoma, transformed follicular lymphoma and mantle cell lymphoma [ 99 ]. This therapy involves isolating T cells from patients or donors and transfecting them with viral vectors containing specific chimeric antigen receptor sequences that recognize previously characterized tumor cell antigens [ 100 , 101 ]. The structure of the CAR consists of an extracellular antigen recognition domain derived from the variable portion of an antibody, a transmembrane domain and an intracellular domain that leads to signal transmission [ 102 ].…”
Section: Chimeric Antigen Receptor (Car) T Cell Based Therapymentioning
confidence: 99%
“…Additionally, while targets may be accessed via infusions in hematologic malignancies or cancers of circulating blood cells such ALL, solid tumors are static and surrounded by a tumor microenvironment. As we have discussed, HCC tumor cells are particularly adept at altering and evading immune responses, ultimately hindering CAR T immune cell trafficking and diminishing efficacy significantly [ 100 , 120 ]. Another issue involves the lack of consistent antigen presentation in solid tumors leading to ineffective target definition even within one etiology [ 101 ].…”
Section: Chimeric Antigen Receptor (Car) T Cell Based Therapymentioning
confidence: 99%